Clinical anatomy, histology, embryology, and neuroanatomy : an integrated textbook - Wikenheiser, Jamie C. (New York, NY : Thieme, 2023)
"Clinical Anatomy, Histology, Embryology and Neuroanatomy: An Integrated Textbook by Jamie Wikenheiser bridges all four anatomical sciences in one volume with clinically focused anatomical text and exceptional illustrations. The book fills a gap in the literature, serving as a one-stop resource for multiple courses and board-review preparation, and also provides an invaluable reference for professional practice. The primary goals of integrating the four sciences into one book are to enhance students' understating of the subject matter, better prepare them for national exams, and most importantly-enable them to deliver optimal care to their future patients"--
Back -- Thorax -- Abdomen -- Pelvis and perineum -- Lower extremities -- Upper extremities -- Head and neck -- Introductory concepts of the nervous system -- Central nervous system -- Peripheral nervous system -- Autonomic nervous system -- Cranial nerves.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Anatomy; MEDICAL / Anatomy; MEDICAL / Histology